Long-term impact of interferon beta-1b in patients with CIS: 8-year follow-up of BENEFIT. Issue 11 (11th November 2013) - Edan, G; Kappos, L; Montalbán, X; Polman, C H; Freedman, M S; Hartung, H-P; Miller, D; Barkhof, F; Herrmann, J; Lanius, V; Stemper, B; Pohl, C; et al.
Abstract : Objective: To examine the long-term impact of early treatment initiation of interferon beta-1b (IFNB1b, Betaferon/Betaseron) in patients with a first event suggestive of multiple sclerosis (MS). Methods: In the original placebo-controlled phase of BENEFIT, patients were randomised to IFNB1b 250 μg or placebo subcutaneously every other day. After 2 years or diagnosis of clinically definite MS (CDMS), all patients were offered open-label IFNB1b treatment for a maximum duration of 5 years. Thereafter, patients were enrolled in an observational extension study for up to 8.7 years. Results: Of the initial 468 patients, 284 (60.7%; IFNB1b: 178 (61.0% of the original arm), placebo: 106 (60.2% of original arm)) were enrolled in the extension study. 94.2% of patients were receiving IFNB1b. Patients originally randomised to IFNB1b had a reduced risk of developing CDMS by 32.2% over the 8-year observation period (HR 0.678; 95% CI 0.525 to 0.875; p=0.0030), a longer median time to CDMS by 1345 days (95% CI 389 to 2301), and a lower annualised relapse rate (0.196 (95% CI 0.176 to 0.218) versus 0.255 (95% CI 0.226 to 0.287), p=0.0012), with differences mainly emerging in the first year of the study. Cognitive outcomes remained higher in the early treated patients. EDSS remained low over time with a median of 1.5 in both arms. Conclusions: These 8-year results provide further evidence supporting early initiation of treatment with IFNB1b in patients with a first event suggestive of MS.